Libraries in the MENA Region: Catalysts for Social and Cultural Impact - Dr. Mohammad Zuheir Bakleh (20618725) (2024)
This Presentation was given by Dr. Mohammad Zuheir Bakleh, (ESCWA) United Nations Economic and Social Commission for Western Asia (Librarians for Library 2024) This presentation highlights the vital role libraries in the MENA region play in fostering social and cultural development. It explores how libraries serve as community hubs, promoting inclusivity, education, and cultural preservation. Through examples and case studies, it emphasizes libraries' contributions to lifelong learning, cultural exchange, and social cohesion. The discussion also addresses challenges such as digital transformation and resource accessibility, offering insights into how libraries can adapt to evolving community needs. It aims to inspire librarians, policymakers, and stakeholders to leverage the transformative potential of libraries for a more informed and connected society. Other Information License: http://creativecommons.org/licenses/by/4.0/ Additional institutions affiliated with: United Nations Economic and Social Commission for Western Asia (ESCWA)